(untitled) (CAHIERS MAGELLANES-NS, 2024)
This research explores the effectiveness of AI-powered personalized learning in enhancing English proficiency and its correlation with employability skills. The purpose of this study is to investigate how AI-driven personalized learning systems impact English language learners' proficiency levels and the development of employability skills such as problem-solving, critical thinking, and creativity. To conduct this research, a mixed-methods approach was employed. Quantitative data was collected through pre-and post-assessments to measure changes in English proficiency levels among participants using AI-powered personalized learning platforms. Qualitative data was gathered through interviews and surveys to understand participants' perceptions of the impact of personalized learning on their employability skills. The results indicate a significant improvement in English proficiency levels among participants who utilized AI-powered personalized learning platforms compared to traditional methods. Moreover, qualitative findings suggest that personalized learning experiences contribute positively to the development of employability skills, as reported by participants. In conclusion, AI-powered personalized learning holds great potential for enhancing English proficiency and fostering the development of employability skills among language learners. By tailoring learning experiences to individual needs and preferences, AI-driven platforms can effectively address learners' weaknesses while reinforcing their strengths. This research highlights the importance of integrating AI technology into language learning initiatives to better prepare individuals for the demands of the modern job market.